Multimodal near‐infrared molecular imaging of ex vivo endometrial carcinoma via CD47‐based targeted tracer - Jing Lei; Dianfeng Tian; Bo Zhang; Hongrui Guo; Huancheng Su; Jinzheng Wei; Shuai Li; Sufen Li; Chao Liu; Xiaofeng Yang; Sanyuan Zhang (Bioengineering & Translational Medicine)
Abstract The detection and complete eradication of early‐stage small tumors during hysteroscopy remains a significant clinical challenge in preserving fertility for young women with endometrial cancer (EC). The purpose of this study is to verify the feasibility of CD47 as an optical molecular imaging (OMI) target for human EC and to achieve precise localization and identification in hysteroscopic surgery. The results demonstrated that CD47 was overexpressed in EC through bioinformatics, immunohistochemistry, and qRT‐PCR. In EC cell lines, CD47‐targeted near‐infrared photoimmunotherapy (NIR‐PIT) induced cytotoxicity in a light dose‐dependent manner. Laser confocal microscopy revealed that CD47 intervention significantly increased the phagocytic effect of macrophages on EC cells. In the mice model of partial tumor resection mediated by CD47‐targeted OMI, compared to group A (immune therapy alone), group C (NIR‐PIT treatment) mice showed a reduced tumor recurrence rate after NIR‐PIT intervention. However, the difference did not reach statistical significance. We then evaluated the effect of CD47‐targeted NIR‐PIT maintenance therapy on tumor recurrence in mice. The results indicated that, compared to untreated animals, the tumor growth rate was slower in the NIR‐PIT group using CD47‐Alexa Fluor 790 (CD47‐AF790), allowing for more sustained tumor control. The freshly isolated whole uterus specimens from EC patients were co‐incubated with CD47‐AF790, and a significantly enhanced contrast of NIR visible images of tumor tissue was observed, demonstrating high sensitivity and specificity (tumor‐to‐background ratio >5.05). Finally, under fluorescence microscopy, specific fluorescent signals are observed on tumor cells. In conclusion, accurate localization and excision of EC can be accomplished by employing CD47 optical molecular contrast agents with OMI technology. This method shows potential as a viable and promising approach for the precise diagnosis of EC.